Implementation of Integrated Project Delivery (IPD) and Building Information Modelling (BIM) in the construction industry - Kaini, Iman (2013)
To increase productivity, the global construction industry has adopted several different project delivery methods and IT tools over the last 10 years. Although there have been previous efforts to define and Implement new generation methods such as Integrated Project Delivery (IPD) and Building Information Modeling (BIM) in the construction industry, but these concepts are still considered new-comers especially in most of developing countries. These countries widely use the traditional methods namely Design-Bid-Build (DBB) and Computer Aided Design (CAD) instead of using them. This study is to analyze Building Information Modeling (BIM) applications potential in the process of Integrated Project Delivery (IPD) and compare it with the Implementation process of conventional tool (CAD) into the Design –bid-build delivery method. For this reason, a case which is a three story residential apartment building located on Tehran is selected. The process of implementation of existing CAD drawings of this case into DBB will be analyzed. Then, the case will be modeled and simulated within BIM applications and its exploiting potential will be identified within IPD. It is expected that the shifting framework path from CAD-DBB into BIM-IPD based on the lessons learned from case study and conducted interviews are developed to clarify these concepts capabilities.